Molecular photo-oscillators based on highly accelerated heterocyclic azo dyes in nematic liquid crystals - Garcia-Amorós, Jaume (2014)
Benzothiazole-pyrrole-based azo dyes enhance greatly their thermal isomerisation rate up to 160 times when they are under the influence of the nematic mean field yielding the LC-based photochromic oscillators with the highest oscillation frequencies reported so far (2.6 kHz at 298 K).